BMP signaling regulates the fate of chondro‐osteoprogenitor cells in facial mesenchyme in a stage‐specific manner. Issue 9 (25th July 2016) - Celá, Petra; Buchtová, Marcela; Veselá, Iva; Fu, Kathy; Bogardi, Jean‐Philippe; Song, Yiping; Barlow, Amanda; Buxton, Paul; Medalová, Jirina; Francis‐West, Philippa; Richman, Joy M.
Abstract : Background : Lineage tracing has shown that most of the facial skeleton is derived from cranial neural crest cells. However, the local signals that influence postmigratory, neural crest‐derived mesenchyme also play a major role in patterning the skeleton. Here, we study the role of BMP signaling in regulating the fate of chondro‐osteoprogenitor cells in the face.Results : A single Noggin‐soaked bead inserted into stage 15 chicken embryos induced an ectopic cartilage resembling the interorbital septum within the palate and other midline structures. In contrast, the same treatment in stage 20 embryos caused a loss of bones. The molecular basis for the stage‐specific response to Noggin lay in the simultaneous up‐regulation of SOX9 and downregulation of RUNX2 in the maxillary mesenchyme, increased cell adhesiveness as shown by N‐cadherin induction around the beads and increased RA pathway gene expression. None of these changes were observed in stage 20 embryos.Conclusions : These experiments demonstrate how slight changes in expression of growth factors such as BMPs could lead to gain or loss of cartilage in the upper jaw during vertebrate evolution. In addition, BMPs have at least two roles: one in patterning the skull and another in regulating the skeletogenic fates of neural crest‐derived mesenchyme. Developmental Dynamics 245:947–962, 2016 . © 2016 Wiley Periodicals, Inc.